Electroanalytical studies - Zhang, Y (2022)
This thesis focuses on electroanalysis using underpotential deposition (UPD) with anodic stripping voltammetry (ASV). This method is developed for arsenic, which shows visually clear signals for sub 10 ppb concentrations in water. In this method arsenic is deposited as As(0) ad-atoms onto the surface of metal electrode, and the ad-atoms are stripped off with a linear potential scan and the Faradaic stripping signal using for quantitative analysis. The novelty and strength of this method is in its use for sub-monolayer UPD rather than bulk deposits as in previous ASV work both generally and specifically for As.